2021
DOI: 10.1055/s-0041-1725230
|View full text |Cite
|
Sign up to set email alerts
|

Brain Abscess in the Current Decade (2010–2019) in India—A Review

Abstract: Brain abscess outcomes have improved in recent years due to advancements in cranial imaging, microbiological techniques, minimally invasive neurosurgical procedures, and effective antibiotic treatments. However, the incidence of brain abscess remains unchanged in developing countries. We searched PubMed and Google Scholar for references using the key words “brain abscess” and “India” and reviewed both retrospective and prospective studies published in peer-reviewed journals in the current decade to understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Brain abscess is an uncommon life-threatening neurological condition with a high mortality rate of up to 36% [ 4 ]. It typically presents with a triad of fever, headache, and focal deficits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brain abscess is an uncommon life-threatening neurological condition with a high mortality rate of up to 36% [ 4 ]. It typically presents with a triad of fever, headache, and focal deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Brain abscess, however, is a rare complication of pneumococcal meningitis, and Streptococcus pneumoniae accounts for only 2% of all bacterial brain abscesses [ 10 ]. In fact, out of 2,216 culture-positive brain abscesses reported in India from 2010 to 2019, only Sarmast et al reported the isolation of Streptococcus pneumoniae in 22 of their patients [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other features include meningitis, multiple infarcts, thrombosis, and aneurysm formation all attributable to vascular invasion by fungal elements. [ 10 ] Although viral etiology is rare, it has high mortality. Radiologically, there is negligible literature on viral cerebral abscess, as viral CNS infections has different traits of presentation including encephalitis (Herpes and Rabies virus), leukoencephalopathy (Human Immunodeficiency Virus), ventriculoencephalopathy (Cytomegalovirus), tissue necrosis, and hemorrhagic foci with sequelae of diffuse gliosis and cyst formation [malacia] with calcification (Coxsackie virus).…”
Section: Discussionmentioning
confidence: 99%
“…Of the micro-organisms affecting the brain, Gram-negative bacilli account for 9–31% of the total infections. [ 10 ] Our case report features CNS melioidosis, caused by Burkholderia pseudomallei , a Gram-negative bacillus endemic to tropical countries. [ 2 ] The rising occurrence of melioidosis in India can be attributed to rising temperatures, humidity, and ultraviolet radiation; the increased prevalence of diabetes mellitus, and immunocompromised status in the population.…”
Section: Introductionmentioning
confidence: 99%